PENERAPAN METODE LEARNING BY DOING SEBAGAI IMPLEMENTASI FILSAFAT PRAGMATISME DALAM MATA KULIAH LINGUISTIK HISTORIS KOMPARATIF - Maslakhah, Siti (Diksi, 2019)
(Title: Application of the Learning by Doing Method as an Implementation of the Pragmatism Philosophy in Comparative Historical Linguistic Subjects). The aim of the article is to describe the implementation of learning by doing method in learning Historical Comparative Linguistics course in Study Program of Indonesian Literature FBS UNY especially on the subject of lexicostatistics and glottochronology. Comparative Historical Linguistics (Linguistik Historis Komparatif/LHK) course is taught in Study Program of Indonesian Literature, Indonesian Language and Literature Education Department, FBS UNY, offered in odd semester and must be taken by the fifth semester students who choose linguistic skill. One of the topics in this course is lexicostatistics and glottochronology. From the results of the examination, it was found that students' understanding and skills of this subject were not entirely satisfactory, therefore learning by doing method was applied so that students had knowledge and skills to determine kinship and a separate period of two languages. In the learning of lexicostatistics and glottochronology subject, the students participating in the class are grouped into several groups. Each group is given the task of calculating the kinship of two languages and then determining the separate period between the two languages. The language studied by each group is different from the other groups. Each group is given the task of finding data in the field. The data is in the form of a lexicon taken from the basic of Swadesh. Students look for respondents who speak the mother tongue of the language who are the object of their research to obtain lexicons from the languages. When the lexicon has been collected, they calculate the kinship and determine the separate period by using the existing formulas. The final results are presented in front of the class. Keyword: learning by doing, pragmatism, comparative historical linguistic